2018
DOI: 10.21037/jtd.2018.05.175
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin1 acts as a suppressor in human lung adenocarcinoma via AKT and ERK1/2 pathway

Abstract: The current results suggested that NRG1 might be a suppressor in the development of LUAD, and its function was related to AKT and ERK1/2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…We further assessed the role of SKA3 in EMT processes [22][23][24][25] but no associations were observed. Upon further analysis, we found that AKT activation strongly correlated with SKA3 expression, and that the expression of MMP following SKA3 silencing decreased in a manner that could be rescued by exogenous AKT overexpression, suggestive that SKA3 influences MMP-2, -7 and -9 to promote of LUAD occurrence and development [26][27][28][29][30][31][32]. These data further suggested that the selective modulation of SKA3 during EGFR-PI3K-AKT signaling in LUADs leads to EGF modulation, with no effects on HGF-signaling.…”
Section: Discussionmentioning
confidence: 94%
“…We further assessed the role of SKA3 in EMT processes [22][23][24][25] but no associations were observed. Upon further analysis, we found that AKT activation strongly correlated with SKA3 expression, and that the expression of MMP following SKA3 silencing decreased in a manner that could be rescued by exogenous AKT overexpression, suggestive that SKA3 influences MMP-2, -7 and -9 to promote of LUAD occurrence and development [26][27][28][29][30][31][32]. These data further suggested that the selective modulation of SKA3 during EGFR-PI3K-AKT signaling in LUADs leads to EGF modulation, with no effects on HGF-signaling.…”
Section: Discussionmentioning
confidence: 94%
“…For example, LPCAT1 regulates LUAD metastasis by activating PI3K/AKT/MYC pathway 27 . NRG1 suppresses human lung adenocarcinoma through AKT and ERK1/2 pathway 28 . FLOT1 affects the progression of lung adenocarcinoma by regulating the Erk/Akt signaling pathway 29 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, neuregulin 1 (NRG1) might be an inhibitor in the progression of LUAD, and its function is related to the AKT and extracellular signal‐regulated protein kinase (ERK)1/2 pathways. 31 Flotillin‐1 (FLOT1) facilitates LUAD cell proliferation, invasion, and migration and inhibits cell apoptosis. In addition, FLOT1 induces epithelial–mesenchymal transition (EMT) and regulates the LUAD cell cycle via activating ERK/AKT cascades.…”
Section: Discussionmentioning
confidence: 99%